Analysis of the competitiveness for commercial banks in Iraq for a period of 2004 – 2012 - كاظم فريد جواد; زين الدين منتصر علي (Journal of Economics and Administrative Sciences, 2015)
This study was conducted on a sample of commercial banks in Iraq, chosen according number of considerations for twenty banks, contained two public banks and eighteen private banks. The goal of research is identify the Activities of commercial banks in Iraq by reaching out and approaching the strengths and weaknesses in their activities by identifying the competitiveness of these banks, In order to achieve this goal we set up certain standard shows us the competitiveness of these banks and reflected their financial performance. The results of research that commercial banks are still suffering from the weakness of the capabilities and effectiveness for influence in the Iraqi economy, Although the commercial banks in Iraq have a long tradition and a long history in the banking industry, but is still limited activity, as I conclude; still commercial banks in Iraq is of from the objectives economic policies commercial banks government. Are still is doing the functions which entrusted to them (since long age) for the re-employment of savings towards the requirements of the Iraqi economy despite the loss of importance. However, these functions carried out by these banks have become routine, such as the distributions of salaries to employees or state ministries. The private banks are a far cry from the requirements of the economy because they are serving their own interests. This can be seen through a particular service request from one of the Iraqi banks. Especially government banks suffer banking its operations: where the procedures and long routine and Dull, It takes a long time for her performance, and multiple administrative levels experienced by the banking service request process for the purpose of getting them. This would certainly lead to increased costs of banking service and secondary expenditures thus lead to lower profits. And the results also showed that private banks are more competitive than state-owned banks according to a criteria of profitability and safety, but the government banks were more competitive And in the market share criteria